Soil organic carbon stock as an indicator for monitoring land and soil degradation in relation to United Nations' Sustainable Development Goals - Lorenz, Klaus; Lal, Rattan; Ehlers, Knut (Land degradation & development, 2019)
Seventeen Sustainable Development Goals (SDGs) adopted in September 2015 aim to end hunger and poverty, to protect the Planet, and to ensure peace and prosperity for all. The soil organic carbon (SOC) stock is a major planetary resource supporting many critically important ecosystem services (ESs) and underpins realization of some of the SDGs at the national level. Thus, decrease in the SOC stock is among the significant universal indicators for land and soil degradation and compromises efforts to achieve the SDGs especially those with reference to food, health, water, climate, and land management. However, there is currently no well‐established relationship (i.e., quantitative evidence) between the SOC stock and the level of ESs attributable to it. Further, basic soil data and monitoring systems including those of SOC stock and its changes are not available for many regions and nations. This uncertainty affects the suitability of using the SOC stock as absolute indicator to monitor changes in land and soil degradation and, particularly, in relation to the SDG monitoring framework. Thus, although the SOC stock is arguably an important indicator for land and soil degradation among others, more research and data on a national level are needed to establish the relationship between the SOC stock and the targets to monitor progress towards achieving the SDGs with reference to food, health, water, climate, and land management. To the best of our knowledge, this is the first review on the suitability of the SOC stock as an indicator for monitoring land and soil degradation with regard to the SDG framework.